The role of ADAM17 in cerebrovascular and cognitive function in the APP/PS1 mouse model of Alzheimer’s disease - Tian, Yanna; Fopiano, Katie Anne; Buncha, Vadym; Lang, Liwei; Suggs, Hayden A.; Wang, Rongrong; Rudic, R. Daniel; Filosa, Jessica A.; Bagi, Zsolt (Frontiers in Molecular Neuroscience, 2023)
The disintegrin and metalloproteinase 17 (ADAM17) exhibits α-secretase activity, whereby it can prevent the production of neurotoxic amyloid precursor protein-α (APP). ADAM17 is abundantly expressed in vascular endothelial cells and may act to regulate vascular homeostatic responses, including vasomotor function, vascular wall morphology, and formation of new blood vessels. The role of vascular ADAM17 in neurodegenerative diseases remains poorly understood. Here, we hypothesized that cerebrovascular ADAM17 plays a role in the pathogenesis of Alzheimer’s disease (AD). We found that 9-10 months old APP/PS1 mice with -amyloid accumulation and short-term memory and cognitive deficits display a markedly reduced expression of ADAM17 in cerebral microvessels. Systemic delivery and adeno-associated virus (AAV)-mediated re-expression of ADAM17 in APP/PS1 mice improved cognitive functioning, without affecting -amyloid plaque density. In isolated and pressurized cerebral arteries of APP/PS1 mice the endothelium-dependent dilation to acetylcholine was significantly reduced, whereas the vascular smooth muscle-dependent dilation to the nitric oxide donor, sodium nitroprusside was maintained when compared to WT mice. The impaired endothelium-dependent vasodilation of cerebral arteries in APP/PS1 mice was restored to normal level by ADAM17 re-expression. The cerebral artery biomechanical properties (wall stress and elasticity) and microvascular network density was not affected by ADAM17 re-expression in the APP/PS1 mice. Additionally, proteomic analysis identified several differentially expressed molecules involved in AD neurodegeneration and neuronal repair mechanisms that were reversed by ADAM17 re-expression. Thus, we propose that a reduced ADAM17 expression in cerebral microvessels impairs vasodilator function, which may contribute to the development of cognitive dysfunction in APP/PS1 mice, and that ADAM17 can potentially be targeted for therapeutic intervention in AD.